Building Stability in Latin American Financial Markets - Liliana Rojas-Suárez; Steven R. Weisbrod (Inter-American Development Bank, Office of the Chief Economist, 1996)
This paper argues that the investor reluctance to make long-term commitments to Latin American financial markets results from experience. In the 1980s, while ex ante real interest rates on Latin American financial assets were usually high, ex-post real interest rates were often highly negative. In the 1990s, policymakers instituted stabilization programs and structural reforms that have improved the environment in which financial markets operate. Based on a review of experiences in the region, this paper shows that, when these opportunities are taken, investor confidence in long-term markets is strengthened.
Keywords: 330